PENGARUH FAKTOR SOSIAL EKONOMI DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA KARYAWAN KOPERASI CU CINTA KASIH TIGAPANAH KABUPATEN KARO - Ginting, Mispa Adelistra Br; Tinambunan, Anitha Paulina (Jurnal Manajemen dan Bisnis, 2019)
This study aims to test and analyze the influence of socioeconomic factors and work motivation on the work performance of the CU Cinta Kasih Tigapanah Cooperative Karo District employees. The sampling technique used is Proportional Random Sampling. The data analysis technique is multiple linear regression. From the results of data processing, socioeconomic factors were found to have a positive and significant effect on the work performance of the CU Cinta Kasih Tigapanah Cooperative employees in Karo District. T test results show that the socio-economic variable variable 2,819> t table 1,668 and with a significant level of 0.009 t table 1,668.